THE CHALLENGE OF (NON) IMPLEMENTATION OF THE OHRID FRAMEWORK AGREEMENT IN THE REPUBLIC OF MACEDONIA - Demush Bajrami; Arburim Iseni (European Scientific Journal, ESJ, 2014)
The Ohrid Framework Agreement (2001), which was designed topreserve the territorial integrity of Macedonia and meet the demands of theAlbanians for constitutional and legal changes in order to achieve equalitybetween Albanians and Macedonians, even though initially it was consideredto be a success not only for Macedonia, but also an example of diplomacy,resulting in stability in this part of the region, did not resolve some of theconcrete issues which were to be resolved in order to maintain the country‘sunity and carry its Euro-Atlantic integration forward. Through a case study,an analysis of the legislation approach is conducted on the use of nationalsymbols, such as using flags of ethnic communities. It is a sure thing that,adopting the Law on languages, national symbols and the ―authenticinterpretation‖ of the Amnesty Law were part of a ―political agreementbetween coalition partners VMRO-DPMNE – BDI.‖ Also, the resocializationof former NLA fighters is an integral part of the process ofmutual reestablishment of trust between the Albanians and Macedonians.But, unfortunately, everything remains at a moral level of a private concern,and not that of institutional concern. Even the new Constitution ofMacedonia has not only defined the domination of the Macedonian people inits Preamble (where the country is described as a state of the Macedonianpeople and then as parts of other people), in addition to defining theMacedonian language as an official state language while the MacedonianOrthodox Church is defined differently. The model of ―power-sharingagreement,‖ now shows an example of weak institutionalization ofconsensual democracy. There is a constant call from Brussels and US for the necessity of reforms and the implementation of the Ohrid Agreement,because without their implementation and without political stability, noeconomic program can bring progress to the country. Open issues should beresolved successfully, and then progress could be made. If Macedonia failsto respect its agreements, then it misses chances to open the doors to NATOand European Union membership.